FDI Political Risks: The New International Context - Filipe, José António (2013)
The understanding of country risk for investors is extremely important. Considering the current international context on geostrategic countries’environment this subject gains additional relevance. The growing global nature of investments makes the country’s risk measurement essential in terms of economic consequences. The international country’s political risk show that companies investments abroad need an involving and multifaceted organization. This paper intends to analyze the conditions of attractiveness and the risks in a political context of a country in which a company intends to invest. The politics’ stability of a country’s government is often determinant to have investments, particularly the ones from an international company. The complexity of this analysis requires the understanding of the way the interrelationships are made. The case of Latin America countries is presented and the new context of China is also analyzed.